Electrochemical sensing platform based on Ag-Fe metal–organic framework for electrocatalytic determination of Atorvastatin - Fatemeh Naji Siyahmazgi; Karim Asadpour-Zeynali (Results in Chemistry)
This article presents a highly sensitive electrochemical sensor that utilizes a metal–organic framework (Ag-Fe MOF) to quickly detect and measure Atorvastatin with high sensitivity using the differential pulse voltammetric (DPV) technique. The sensor was developed using a straightforward synthesis technique to detect Atorvastatin. The synthesized metal–organic framework was characterized through the use of various analytical techniques, including Fourier-transform infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), element map, and electrochemical techniques. The Atorvastatin oxidation calibration graph was plotted using the differential pulse voltammetry technique under the best possible conditions. The calculated detection limit of 0.3 μM and linear ranges of 0.66–40 μM and 40–194.69 μM were found for Atorvastatin oxidation. The findings demonstrate that the sensor that was developed demonstrates favorable repeatability and exceptional stability when used for the determination of Atorvastatin. Notably, one of the significant achievements of this sensor is the ability to determine Atorvastatin in tablets and biological samples.